2004
DOI: 10.1002/ange.200300635
|View full text |Cite
|
Sign up to set email alerts
|

Hoch effiziente asymmetrische Katalyse durch doppelte Aktivierung von Nucleophil und Elektrophil

Abstract: Die Entwicklung neuer Hochleistungs‐Katalysatoren für asymmetrische Katalysereaktionen ist für die Organische Chemie von dauerhaftem Interesse. Eine aktuelle Methode bei der stereoselektiven Synthese ist die Verwendung einer Kombination von Lewis‐Säure und Lewis‐Base. Der Synergieeffekt durch die Aktivierung mithilfe von zwei oder mehr reaktiven Zentren führt zu hohen Reaktionsgeschwindigkeiten und zu einer hervorragenden Übertragung der stereochemischen Information. Obwohl durch die unerwünschte Reaktion der … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
26
0
4

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(30 citation statements)
references
References 226 publications
0
26
0
4
Order By: Relevance
“…Cooperative catalysis, [6] the simultaneous binding and activation of reacting partners resulting in both pre-organization of the substrates and stabilization of the transition state structures, is a fundamental principle in enzymatic catalysis. Therefore, recently, much effort has focused on the development of efficient bifunctional organocatalysts that effectively orient sub- …”
Section: Introductionmentioning
confidence: 99%
“…Cooperative catalysis, [6] the simultaneous binding and activation of reacting partners resulting in both pre-organization of the substrates and stabilization of the transition state structures, is a fundamental principle in enzymatic catalysis. Therefore, recently, much effort has focused on the development of efficient bifunctional organocatalysts that effectively orient sub- …”
Section: Introductionmentioning
confidence: 99%
“…[2,3] Acid-base dual-activation catalysis has received much attention for highly efficient nucleophilic reactions, including carbon-carbon bond-forming reactions. [4] In base-catalyzed carbon-carbon couplings, nucleophilic precursors are activated by basic catalysts to generate nucleophiles by abstraction of their acidic parts, such as acyl groups and a-hydrogen atoms, and then, the nucleophiles attack electrophiles. On the other hand, decreasing the levels of the lowest-unoccupied molecular orbital (LUMO) of the electrophiles can be readily achieved by coordination activation of Brønsted or Lewis acidic catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…[10] We report here the first enantioselective catalysis using a chiral bisphosphazide (1 a) complexed with lithium salts, by which direct, enantioselective 1,4-addition of dialkyl malonates to acyclic enones can be efficiently accomplished (Scheme 1). The asymmetric direct Michael addition of malonates to enones is a representative reaction in modern asymmetric catalysis, [11] and known metallic [12] and non-metallic [13,14] catalysts developed for this purpose are also effective for other base-catalyzed asymmetric processes. [11] We also present a possible application of the phosphazide Keywords: asymmetric catalysis · basicity · lithium · Michael addition · phosphazene base Abstract: Chiral bisphosphazides complexed with lithium salts efficiently catalyze the direct enantioselective 1,4-addition of dialkyl malonates to acyclic enones.…”
Section: Introductionmentioning
confidence: 99%
“…The asymmetric direct Michael addition of malonates to enones is a representative reaction in modern asymmetric catalysis, [11] and known metallic [12] and non-metallic [13,14] catalysts developed for this purpose are also effective for other base-catalyzed asymmetric processes. [11] We also present a possible application of the phosphazide Keywords: asymmetric catalysis · basicity · lithium · Michael addition · phosphazene base Abstract: Chiral bisphosphazides complexed with lithium salts efficiently catalyze the direct enantioselective 1,4-addition of dialkyl malonates to acyclic enones. Spectroscopic studies on the stoichiometry of the bisphosphazide and lithium salt have indicated the formation of a 1:1 species as the active enantioselective catalyst.…”
Section: Introductionmentioning
confidence: 99%